Strategi Pemasaran Bunga Potong Di NMM Florist Kec. Parongpong Kab. Bandung Barat (Studi Kasus) - Mulyana, Yayan; Rosid, Abdul; Pardomuan, Ferdian; Luthfiyyah, Melsa Nawal (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2025)
This research aims to analyze and describe the marketing strategy of cut flowers at NMM Florist in Parongpong District, West Bandung Regency. The research method used is qualitative-descriptive. Data collection techniques used are observation, interviews, questionnaires, documentation, and literature study. Data analysis techniques use triangulation with the Miles and Huberman model and SWOT analysis. The problems identified include the lack of marketing strategies implemented by the business, such as no product improvement, standard product assembly processes, limited advertising through WhatsApp Business, and inadequate use of Instagram for promotion. The research results show that the marketing strategy analysis involves interrelated elements such as market selection, product, price, distribution, and promotion. The SWOT analysis highlights strengths, weaknesses, opportunities, and threats. Based on the analysis, recommended strategies for NMM Florist include : Maintaining product quality and price, Forming mutually beneficial partnerships to expand marketing areas, Utilizing technology for promotions, Improving packaging design, Increasing production before the rainy season, Innovating flower arrangements, Expanding marketing areas and promotions to attract customers. Business owners need to understand how to implement SWOT analysis to improve marketing strategies. Keywords : Strategy, Marketing, Cut Flowers